Tree slenderness and stability of Brazilian pine in a secondary forest - Vinicius Costa Cysneiros; Eduardo Luz de Souza; Leandro Correa Pinho; Allan Felipe Vuolo; Isabelle Roisin Soler Pereira (Floresta e Ambiente)
Abstract The aim of this study was investigating the factors that render Araucaria angustifolia trees less stable in secondary forests to support the species conservation strategies. Nine plots were allocated in a Mixed Atlantic Forest where, buckling damage was observed among Araucaria’s trees. Then stability was evaluated using the tree slenderness coefficient (TSC), considering TSC≥80 as the critical stability threshold of buckling and breakage. Generalized additive models were fitted to describe variations in TSC in response to tree and plot characteristics. The tree-level characteristics DBH, TH, and canopy position significantly influenced the TSC, as well as competition with larger trees at plot-level. Slenderness decreased with tree size and increased with light competition, with small trees under competition having TSC values beyond the critical stability threshold. Therefore, to maintain more resistant and stable stands, small trees under intense competition should receive more attention and be favored in thinning procedures.